Coulson and Richardson's chemical engineering. - Chhabra, R. P. (Butterworth-Heinemann, 2018)
Coulson and Richardson's Chemical Engineering has been fully revised and updated to provide practitioners with an overview of chemical engineering. Each reference book provides clear explanations of theory and thorough coverage of practical applications, supported by case studies. A worldwide team of editors and contributors have pooled their experience in adding new content and revising the old. The authoritative style of the original volumes 1 to 3 has been retained, but the content has been brought up to date and altered to be more useful to practicing engineers. This complete reference to chemical engineering will support you throughout your career, as it covers every key chemical engineering topic. Coulson and Richardson's Chemical Engineering: Volume 1A: Fluid Flow: Fundamentals and Applications, Seventh Edition, covers momentum transfer (fluid flow) which is one of the three main transport processes of interest to chemical engineers. Covers momentum transfer (fluid flow) which is one of the three main transport processes of interest to chemical engineers Includes reference material converted from textbooksExplores topics, from foundational through technicalIncludes emerging applications, numerical methods, and computational tools